ANTIDEPRESSANT-LIKE ACTIVITY OF TRANS-ANETHOLE IN UNSTRESSED MICE AND STRESSED MICE: Department of Pharmaceutical Sciences, Guru Jambheshwar University of Science and Technology, Hisar -125 001 (Haryana) - DINESH DHINGRA,; SUDHA, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The present study was undertaken to investigate the antidepressant potential of trans-anethole in unstressed and stressed male mice. Methods: Swiss albino male mice were exposed to chronic unpredictable mild stress for 21 successive days. Simultaneously, trans-anethole (12.5 mg/kg, 25 mg/kg, and 50 mg/kg) and fluoxetine (20 mg/kg) per se were administered for 21 successive days to separate groups of unstressed and stressed mice. The effect of drugs on depressive-like behavior of mice was tested by tail suspension test (TST) and sucrose preference test. Results: Trans-anethole (25 mg/kg) and fluoxetine significantly decreased the immobility period of unstressed and stressed mice in TST as compared to their respective control. These drugs significantly restored the reduced sucrose preference (%) in stressed mice. Trans-anethole did not show any significant effect on locomotor activity of mice. Antidepressant-like activity of trans-anethole (25 mg/kg) was found to be comparable to fluoxetine. Trans-anethole and fluoxetine significantly inhibited brain monoamine oxidase-A (MAO-A) activity, decreased plasma nitrite, brain malondialdehyde, and increased brain reduced glutathione levels and catalase activity in unstressed and stressed mice. The drugs significantly reversed stress-induced increase in plasma corticosterone levels. Conclusion: Trans-anethole produced significant antidepressant-like activity in unstressed and stressed mice, possibly through inhibition of brain MAO-A activity and alleviation of oxidative stress. Reversal of stress-induced increase in plasma corticosterone levels might also be responsible for antidepressant-like activity of trans-anethole in stressed mice.